Application of the Problem Based Learning (PBL) Learning Model Using Puzzle Media in Pancasila Education Subjects to Increase the Learning Motivation of Class IX 7 Students at SMP Negeri 30 Palembang - Alfiandra Alfiandra; Ainun Fadilah; Annisa Maula; Dhea Riskiana Anisa; Ernita Dita Tiara; Febby Hovia Anggrayni; Fitriatun Maesaroh (Journal of Education Technology Information Social Sciences and Health, 2024)
Motivation is an emotional drive within a person to be able to do something, more than that to complete something, when someone is motivated to do something, the enthusiasm within him is to complete or achieve a predetermined goal. Motivation is a supporting factor for the success of students' learning process, without high motivation it will hinder the students' learning process. This research is Classroom Action Research with a collaborative approach. The sample for this research was 38 students in class IX 7 of SMP Negeri 30 Palembang, consisting of 17 women and 21 men. The data collection methods used in this research are observation and documentation. The results of research on student learning motivation before learning was carried out using puzzle media/Pre-cycle 23% were at low motivation, then in Cycle I it was at 58% and Cycle II was at 79%. From these results it can be seen that the achievement of learning motivation results for class IX 7 students at SMP Negeri 30 Palembang increased by implementing Puzzle media in the Pancasila Education subject.